Clines in Africa: does size vary in the same way among widespread sub‐Saharan monkeys?. (21st September 2012) - Cardini, Andrea; Dunn, Jason; O'Higgins, Paul; Elton, Sarah; Riddle, Brett
Abstract Aim We characterize and compare patterns of clinal size variation among diverse widespread sub‐Saharan monkeys with the aim of identifying commonalities and differences in biogeographical variation. Thus, we accurately quantify nonlinear clines in representatives of the main lineages of widespread sub‐Saharan terrestrial and arboreal monkeys, and provide a crude numerical estimate of the strength of similarities across taxonomic groups. Location Sub‐Saharan Africa. Methods Variations of skull centroid size, as a proxy for body mass, were modelled over sub‐Saharan Africa within two terrestrial monkey species (Papio hamadryas and Chlorocebus aethiops) and two arboreal monkey taxa (Procolobus (Piliocolobus) sp., and the superspecies Cercopithecus nictitans–Cercopithecus mitis) using inverse distance weighting, thin‐plate splines and kriging. The model with the highest cross‐validated accuracy was used to produce contour plots that visualized clines and predicted size at equally spaced localities across overlapping areas of distribution ranges. Correlations among these predictions were used as a similarity measure among clines. Results Irrespective of phylogenetic distances and ecological differences, all groups showed similarities in clinal size over central Africa: large animals mostly live in and around the tropical forest of the Congo basin; size declines rapidly towards the Horn of Africa and the coasts of Kenya and Tanzania. Size also tends to decrease in western Africa but clinal patterns in this region vary, with vervets (Chlorocebus aethiops) exceptionally showing a size increase. Main conclusions Similarities in patterns of size across diverse monkey groups were found. Nonetheless, complexity in clines and a degree of heterogeneity across groups were evident, which is unlikely to be compatible with the exclusive effect on size of a single main environmental factor. Primary productivity may be most significant in relation to the consistent observation of large sizes in and adjacent to the central African tropical forest belt. Complex clines, such as those of African monkeys, are difficult to compare visually and data collection from evenly sampled sets of localities, where all species of interest may be found, is often impractical or simply not feasible for primates and other protected animals. The development of improved quantitative methods for the description and comparison of clines in mammals and other organisms is required.